Contribution in tracing the origin and evolutional history of almond around the Mediterranean basin - Gouta H.; Ksia E.; Ben Ayed R.; Gogorcena Y.; Rebai A. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Results regarding the origin and domestication steps of almond and its dissemination around the Mediterranean basin are very controversial. The general belief is that the domestication was in the eastern side and then its dissemination to the western part was through the different trade routes. A recent study has proved using a combination of nuclear and chloroplast microsatellites a westward dispersal of almond and a long-standing presence of domesticated almond in northern Africa. In order to contribute to this discussion, new interpretation of the previous study using 10 SSRs to analyse 82 almond accessions from different origins was undertaken. The dendogram based on the similarity matrix presented four main clusters. In group A were present the majority of the local genotypes that originate from the centre and the south. Contrarily, all cultivars from the north were in group C and clustered with the European and American genotypes. In fact, the Bayesian-based analysis endorses a two divergent population structure. Accordingly, our study supports the presence of two genetically distinct groups. One located in the north and a second in the central and southern part that may be issued from mutational processes. Thus, our work supports the hypothesis of the French team regarding a native existence of almond in North Africa and a possible westward dispersal.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)